Analysis of the Achievement of the Quality of Education for MSME Actors in 34 Provinces of Indonesia in 2021 - Indri Arrafi; Alma Syafitri; Sugianto Sugianto; Jubaedah Jubaedah; Praptiningsih Praptiningsih (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
The quality of education for MSME actors in Indonesia shows significant regional disparities, which impact their ability to compete in the market. This research aims to assess the achievement of quality education for MSME actors in the 34 provinces of Indonesia in 2021, focusing on key indicators such as high school completion rates, literacy rates, ICT skills, high school repetition rates, and higher education enrollment ratios. The research employs the Qualitative Comparative Analysis (QCA) method to analyze the educational conditions across provinces. The findings reveal a considerable gap in educational outcomes, with provinces like DI Yogyakarta and DKI Jakarta showing better educational performance, while Papua faces significant challenges. The research concludes that improving access to quality education for MSMEs is essential for fostering innovation, enhancing business performance, and contributing to national economic growth. This research highlights the need for targeted government interventions to address the educational disparities in Eastern Indonesia and other underperforming regions.